Developing Spatial Imagination by Teaching Students the Elements of Geometry - I. U. Izbosarov; D. T. Jamilova (International Journal on Integrated Education, 2021)
This article emphasizes the value of descriptive geometry in building students' spatial imagination and gives information for their engineering graphics research work.